(untitled) - Bhave, P ramod R. (Pangbourne, 2003)
In case of water distribution networks, engineers are concerned with two aspects: Analysis of networks for operational purposes, and as an intermediate step in design by the traditional trial-and-error apporoach; and economical design of new networks, and strengthening and expansion of existing ones.
Keywords: Remote submersibles,Soft computing,Underwater exploration,Phần mềm máy tính,Thăm dò nguồn nước; Industrial applications,Công nghệ ứng dụng,Quốc hội,Quốc hội